Elaboración de un plan de mantenimiento para la maquinaria pesada de la división de obras públicas de La Dorada Caldas (2022)
In this project the development of a maintenance plan focused on the heavy machinery of the public works division of the municipality of La Dorada, Caldas, Colombia, is carried out. The purpose of the plan is to optimize the operation of the machinery, thus achieving an increase in its productivity, in addition to reducing stoppages due to failures, maintenance times and operating cost overruns. The maintenance plan is aimed at preventing machinery failures, for which a strategic method must be proposed that addresses the different aspects and elements necessary for the optimization of the fleet of vehicles involved in construction services and other similar activities. Within the project, a descriptive methodology with a mixed approach (qualitative and quantitative) is approached, which allows the construction of the different formats required for the control and execution of the activities necessary for the subsequent implementation of the present proposal. The work is developed with the premise that over the years organizations are in a continuous process of improvement; resorting to the standardization of procedures and technification, for this they have sought that their machinery is in the best operating conditions, thus arising the maintenance programs that allow to preserve and prolong the life of the mechanisms. Therefore, this project suggests a maintenance plan aimed at the prevention of failures, optimization of equipment and machinery, and at the same time the development of the relevant formats. The characterization of the assets, diagnosis of current maintenance conditions, elaboration of the plan and finally the financial aspects are studied.